Investigation of Mild Steel Corrosion in the Cement Production Associated with the Usage of Secondary Fuels. (18th September 2020) - Thieme, Michael; Bergmann, Ute; Kiesewetter, Anja; Wehry, Tobias; Potzger, Kay; Zarzycki, Arkadiusz; Marszalek, Marta; Worch, Hartmut
Abstract : The present work deals with the corrosion of mild steel (1.0037) used as the outer construction material of the preheater of a modern industrial cement production facility. The facility uses secondary fuels, which introduce considerable amounts of corrosive species. The situation at the examination sites in the preheater zone is tracked over a period of two years including operation and shut-down periods. The investigation is focused on (i) the acquisition of the underlying physicochemical conditions, such as moisture, temperature, and contamination data at the examination site of the preheater, (ii) the multianalytical identification of the formed corrosion products using scanning electron microscopy combined with energy-dispersive X-ray analysis, infrared spectrometry, Raman spectrometry, X-ray diffractometry, and Mö β bauer spectrometry, and (iii) voltammetric and EIS laboratory investigations using model solutions. It was evidenced that corrosion takes place at a temperature level of about 100°C in the presence of moisture and oxygen as well as chloride ion as a consequence of the usage of secondary fuels. Typical hot-gas corrosion could be excluded under the current conditions. Appearance, structure, and nature of the corrosion products were found to be not mainly dependent on the varied length of exposure, but on the conditions of the hosting preheater intake. In addition to different FeOOH phases and hematite, magnetite was found, dependent on the oxygen concentration in the process gas. The decisive role of oxygen as key factor for the corrosion rate was electrochemically confirmed.